2021
DOI: 10.1111/cmi.13306
|View full text |Cite
|
Sign up to set email alerts
|

Very long O‐antigen chains of Salmonella Paratyphi A inhibit inflammasome activation and pyroptotic cell death

Abstract: Salmonella Paratyphi A (SPtA) remains one of the leading causes of enteric (typhoid) fever. Yet, despite the recent increased rate of isolation from patients in Asia, our understanding of its pathogenesis is incomplete. Here we investigated inflammasome activation in human macrophages infected with SPtA. We found that SPtA induces GSDMD‐mediated pyroptosis via activation of caspase‐1, caspase‐4 and caspase‐8. Although we observed no cell death in the absence of a functional Salmonella pathogenicity island‐1 (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Typhoid fever disease and host-response to S. Typhi infection is largely attributed to the function of the Vi polysaccharide capsule and its associated regulator, TviA encoded on SPI-7 [17][18][19][20]. Nonetheless, since SPA does not harbor the SPI-7, nor expresses the Vi capsule, different mechanisms such as long O antigen chains in the LPS of SPA were suggested to play a role in evasion from the host-immune response and the clinically indistinguishable enteric fever disease caused by SPA and S. Typhi [21,22]. Previously, we showed that in Salmonella culture grown in LB to the late logarithmic phase, SPI-1 genes and T3SS-1 effectors are expressed and secreted at significantly lower levels by SPA compared to S. Typhimurium (STM) [23], and demonstrated differences in the regulatory setup of the flagella-chemotaxis pathway between these serovars [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Typhoid fever disease and host-response to S. Typhi infection is largely attributed to the function of the Vi polysaccharide capsule and its associated regulator, TviA encoded on SPI-7 [17][18][19][20]. Nonetheless, since SPA does not harbor the SPI-7, nor expresses the Vi capsule, different mechanisms such as long O antigen chains in the LPS of SPA were suggested to play a role in evasion from the host-immune response and the clinically indistinguishable enteric fever disease caused by SPA and S. Typhi [21,22]. Previously, we showed that in Salmonella culture grown in LB to the late logarithmic phase, SPI-1 genes and T3SS-1 effectors are expressed and secreted at significantly lower levels by SPA compared to S. Typhimurium (STM) [23], and demonstrated differences in the regulatory setup of the flagella-chemotaxis pathway between these serovars [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Although the O antigen section of the LPS is not supposed to be involved in caspase 11 activation, several studies previously reported that it could interfere with activation of the non-canonical inflammasome. Salmonella and Shigella both trigger low pyroptosis whereas mutant strains with shorter or completely lacking O antigen induce higher levels of pyroptosis (Mylona et al , 2021; Watson et al , 2019). It was believed that the full-length O antigen could interfere with the lipid A binding to caspase 11 (Mylona et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella and Shigella both trigger low pyroptosis whereas mutant strains with shorter or completely lacking O antigen induce higher levels of pyroptosis (Mylona et al , 2021; Watson et al , 2019). It was believed that the full-length O antigen could interfere with the lipid A binding to caspase 11 (Mylona et al ., 2021). Our results showing that the leptospiral LPS binds caspase 11 through an atypical interaction, independent of the CARD domain, further support the hypothesis that steric hindrance could prevents caspase 11 activation by E. coli LPS and consequent pyroptosis induction.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is involved in S . Typhimurium pathogenesis, the role of fepE in immune responses is still unclear [ 15 , 16 ]. Thus, we would like to alter wzz ST to explore the effect of the OAg length on the immunogenicity of both the Salmonell a vector and the delivered OAg in the presence of fepE .…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are three OAg lengths in Salmonella: short (S-OAg, < 15 RUs), long (L-OAg, 16 to 35 RUs), and very long (VL-OAg, > 100 RUs), with wzz ST controlling the lower modal length pattern and fepE controlling the high molecular weight (HMW) LPS modal length (> 100 RUs) [12]. In E. coli, however, OAg length was classified as short (7)(8)(9)(10)(11)(12)(13)(14)(15)(16), intermediate (10)(11)(12)(13)(14)(15)(16)(17)(18), and long (16)(17)(18)(19)(20)(21)(22)(23)(24)(25) [13]. In a previous study, we discovered that the OAg lengths of wild-type E. coli O2 and S. Typhimurium differed in silver-stained SDS-PAGE [14].…”
Section: Introductionmentioning
confidence: 99%